Length–weight relationships for seven fish species of the Napo River, Upper Amazon, Peru. (28th June 2017) - Garcia‐Ayala, J. R.; Brambilla, E. M.; David, G. S.; Benine, R. C.; Sanchez, H.
Summary: Length–weight relationships (LWR) were estimated for seven fish species from the Napo River and its main tributaries, Arabela and Curaray rivers, Amazon basin, Peru. A total of 652 specimens were sampled between 2012 and 2014 using seines and gillnets. This study reports new maximum total length for four species and new LWR and maximum total weight records for three and five species, respectively.